Embedding Arts and Humanities in the Creative Economy: The Role of Graduates in the UK. (June 2014) - Comunian, Roberta; Faggian, Alessandra; Jewell, Sarah
The recent change in funding structure in the UK higher education system has fuelled an animated debate about the role that arts and humanities (A&H) subjects play not only within higher education but more broadly in the society and the economy. The debate has engaged with a variety of arguments and perspectives, from the intrinsic value of A&H, to their contribution to the broader society and their economic impact, particularly in relation to the creative economy, through knowledge exchange activities. The paper argues that in the current debate very little attention has been placed on the role that A&H graduates play in the economy, through their work after graduation, and specifically in the creative economy. Using Higher Education Statistical Agency data, we analyse the performance of A&H graduates (compared with other graduates) and particularly explore how embedded they are with the creative economy and its associated industries. The results highlight a complex intersection of different subdisciplines of the A&H with the creative economy but also reveal the salary gap and unstable working conditions experienced by graduates in this field.